2015
DOI: 10.14737/journal.jahp/2015/3.1.21.27
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ethanolic Extract of Carica papaya leaves as a Substitute of Sulphanomide for the Control of Coccidiosis in KABIR Chickens in Cameroon

Abstract: | Coccidiosis remains one of the main diseases affecting performance in poultry. This work was aimed at evaluating the efficacy of an ethanolic leaf extract of Carica papaya with regard to growth, parasitological and haematological parameters in Eimeria-infected KABIR chickens. Fresh leaves were harvested, dried in gentle heat, ground and sieved powder was used to prepare the ethanolic extract. Chickens were infected with 3200 Eimeria oocysts until they began shedding oocysts in their faeces. The ethanolic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 10 publications
7
21
0
Order By: Relevance
“…Dietary supplemention of genistein and hesperidin increased the immune organ index for bursa, spleen (21 days) and thymus (42 days) in this study, which is in agreement with a recent study of flavonoid-rich extract (Dong et al, 2007), which reported a significantly increased sizes of thymus, bursa and spleen. A similar effect of ethanolic extract of Carica papaya leaves was reported in case of coccidia-challenged chickens, which resulted in the increase in size of heart, thymus and bursa (Nghonjuyi et al, 2015). Bursa is recognized as the most responsive immune organ of chicken for microbial infections (Hanieh et al, 2010).…”
Section: Discussionsupporting
confidence: 56%
“…Dietary supplemention of genistein and hesperidin increased the immune organ index for bursa, spleen (21 days) and thymus (42 days) in this study, which is in agreement with a recent study of flavonoid-rich extract (Dong et al, 2007), which reported a significantly increased sizes of thymus, bursa and spleen. A similar effect of ethanolic extract of Carica papaya leaves was reported in case of coccidia-challenged chickens, which resulted in the increase in size of heart, thymus and bursa (Nghonjuyi et al, 2015). Bursa is recognized as the most responsive immune organ of chicken for microbial infections (Hanieh et al, 2010).…”
Section: Discussionsupporting
confidence: 56%
“…The results showed that there were no significant differences due to selenium source. These results are in agreement with some previous studies that indicated that dietary inclusion of antioxidants could not improve the performance of birds (Nghonjuyi et al, 2015). This might be due to adequacy for the experimental diets (Ensminger et al, 1990).…”
Section: Synthesis and Characterization Of Nano Semetsupporting
confidence: 93%
“…are the most mentioned ethnoveterinary medicine used in controlling diseases. Papaya leaves were used as ethnoveterinary plants for backyard pigs and chickens in Trinidad and Tobago (Lans et al 2007) and used for controlling coccidiosis of chickens in Cameroon (Nghonjuyi et al 2015). In the current study, Pelung keepers claimed that Papaya leaves are beneficial for some disease treatments mostly for controlling parasitic worms.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Pelung keepers claimed that Papaya leaves are beneficial for some disease treatments mostly for controlling parasitic worms. Papaya leaves contain papain, a proteolytic enzyme, which is capable of digesting worms or other parasitic cells (Nghonjuyi et al 2015;Al-Fifi 2007). The antiinflammatory property of papaya leaves with high concentrations of vitamin A may protect caeca epithelium cell of chickens and build body resistance to coccidian (Al-Fifi 2007;Nghonjuyi et al 2015).…”
Section: Discussionmentioning
confidence: 99%